Buddhism in Spain: a Post-Secular and Post-Religious Avant Garde? - Díez de Velasco, Francisco (’Ilu. Revista de Ciencias de las Religiones, 2025)
Being Buddhist is perceived in different and even antithetical ways. Those who consider it a religion have no problem, for example, registering their religious communities in the Register of Religious Entities (RER) of the Spanish Ministry of the Presidency and/or Justice. On other occasions, however, they clearly show that they should not be considered a religion and, therefore, when they institutionalise themselves, they do so as cultural associations and not as religious entities or communities. There are also groups that are committed to a Buddhism that they explicitly call atheistic, which, therefore, proposes that it is an option that could be judged as antithetical to what is usually understood as religion and that is fully encompassed in what we could call the post-secular and post-religious magma. Buddhism in Spain offers good examples of this problem of characterisation or definition, which adds a peculiar perspective given the great diversity that characterises groups, schools, but also individuals who consider themselves or identify themselves, albeit in a lax or tortuous way, as Buddhists. It allows us to offer elements to think about the invisibilisation (and stigmatisation) of religion in current societies, using the Spanish case as an example.